2020
DOI: 10.1016/j.ccell.2019.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Roles for Branched-Chain Amino Acid Metabolism in Cancer

Abstract: Metabolic pathways must be adapted to support cell processes required for transformation and cancer progression. Amino acid metabolism is deregulated in many cancers, with changes in branched-chain amino acid metabolism specifically affecting cancer cell state as well as systemic metabolism in individuals with malignancy. This review highlights key concepts surrounding the current understanding of branched-chain amino acid metabolism and its role in cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
215
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 310 publications
(225 citation statements)
references
References 96 publications
7
215
0
3
Order By: Relevance
“…BCAA catabolism is mediated by the cytosolic branched-chain amino acid transaminase 1 (BCAT1) and mitochondrial branched-chain amino acid transaminase 2 (BCAT2) which transfer the amino groups from BCAAs to α-KG to produce branched-chain α-keto acids (BCKAs) and glutamate. BCAA breakdown can not only provide carbon for synthesis of metabolites to fuel TCA cycle which can contribute to energy production but also supply nitrogen for de novo nucleotide and non-essential amino acid biosynthesis in cancer (21). It has been shown that plasma BCAAs levels are elevated in early-stage pancreatic cancers driven by mutant KRAS (22).…”
Section: Krasmentioning
confidence: 99%
“…BCAA catabolism is mediated by the cytosolic branched-chain amino acid transaminase 1 (BCAT1) and mitochondrial branched-chain amino acid transaminase 2 (BCAT2) which transfer the amino groups from BCAAs to α-KG to produce branched-chain α-keto acids (BCKAs) and glutamate. BCAA breakdown can not only provide carbon for synthesis of metabolites to fuel TCA cycle which can contribute to energy production but also supply nitrogen for de novo nucleotide and non-essential amino acid biosynthesis in cancer (21). It has been shown that plasma BCAAs levels are elevated in early-stage pancreatic cancers driven by mutant KRAS (22).…”
Section: Krasmentioning
confidence: 99%
“…The downstream mechanism of how BCAAs are affecting cell survival in ATM inhibited cells remains unknown. The irreversible step of BCAA metabolism via the branched chain alpha-keto acid dehydrogenase (BCKDH) complex generates mitochondrial NADH in addition to providing acetyl-and succinyl-CoA to the TCA cycle, and BCAAs have been shown to inhibit ROS (Sivanand and Vander Heiden, 2020). Since ATM inhibition increases ROS (Valentin-Vega et al, 2012), which in turn can promote AMPK activation (Rabinovitch et al, 2017), it is possible that BCAAs are consumed to promote redox homeostasis.…”
Section: Macropinocytosis Induced By Atm Inhibition Increases Bcaa Upmentioning
confidence: 99%
“…RT cells show an active oxidative metabolism RT4 cells show increased consumption of arginine, glutamine, BCAAs and serine, along with increased excretion of formate with respect to 5637 cells (Figure 3). All these compounds are related to metabolic pathways that occur inside the mitochondria, require an active oxidative metabolism, and were already found altered in different tumors and cancer cell lines [9][10][11]. RT4 cells show also a higher serine consumption than the other two cell lines, along with a higher excretion of a product of its catabolism, formate, a further con rmation of an active mitochondrial activity and active oxidative phosphorylation metabolism (OxPhos) [12].…”
Section: Glycolysis Is the Most Active Metabolic Pathway In 5637 Cellsmentioning
confidence: 98%